Abraham Valdelomar: patriotic sentiment - Valenzuela Noguera, Ezequiel (2020)
This article is about the literary and the scense of Abraham Valdelomar Pinto (1888-1919) self-proclaimed as «El Conde de Lemos», in the Aristocratic Republic stage as historical-political background. Abraham Valdelomar stands, in his political-literary action, between two great and important currents or generations: the 900’s and the Centennial.